THEORETICAL MECHANICS OF 6-DIMENSIONAL (6D) CENTRAL-FORCE MOTION WITH TANGENTIAL OSCILLATIONS. - Enaibe, Edison A.; Erhieyovwe, Akpata; Omosede, Osafile E. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2014)
The relevance of the Central - force motion in the macroscopic and microscopic frames warrants a detailed study of the theoretical mechanics associated with it. So far, researchers have only considered central - force motion, as motion only in the translational and rotational elliptical plane with polar coordinates. However, the theoretical knowledge advanced by these researchers in line with this type of motion is scientifically restricted as several possibilities are equally applicable. In order to make the mechanics of a Central - force motion sufficiently meaningful, we have in this work extended the theory which has only been that of translational and rotational in the elliptical plane, by including fictitious radii and spin oscillations of the body about the axis of rotation. In this work, we used the methods of Newtonian mechanics to establish the new central-force field obeyed by the motion of a body, when the effect of spin oscillation is added. The new central-force field comprises of the radial accelerations, translational orbital angular velocity and the oscillating spin angular velocities. The energy conveyed in the spin oscillating phase increases as the orbital oscillating angles above or below the horizon of the elliptical plane is increased.